Why a U.S.-China Trade Deal will not Ensure an Effective Global Trade Governance - Kazzi, Habib (European Scientific Journal, ESJ, 2019)
This contribution makes the case for the building of a constructive partnership between China and global players, including the United States, the only way to tackle China’s trade policy challenges and ensure effective global trade governance. After months-long negotiations, the United States and China may put the finishing touches on a trade deal to end their trade war. Despite advances secured by the U.S., it should be admitted that once again, when it comes to negotiations with China, it is a matter of much ado about nothing. China will remain a unique and pressing challenge for the WTO and its trading partners. It appears that China’s trade distortions are the outcome of a singular China’s political and legal system promoting a socialist market economy with a state-led and mercantilist trade regime. The trade deal, through its enforcement offices, will not be able to prevent the U.S. from imposing unilateral sanctions against China, nor will it be able to minimise strategic competition between the two States. In this context, pursuing unilateral measures and sanctions to obtain structural reforms protecting U.S. workers, farmers and businesses is largely a futile exercise. Rather, modernizing the China’s economic and legal architecture than reforming it should be the cornerstone of a realistic, multifaceted and long-term approach based on a constructive diplomacy, including the creation of new institutions such as a bilateral investment treaty with China and the accession to the Trans- Pacific Partnership, as well as a joint working group on WTO reform with like-minded States capable of exerting upward pressure on China so as to revitalize WTO rules and functions.